Phase 1b Trial of Ficlatuzumab, a Humanized Hepatocyte Growth Factor Inhibitory Monoclonal Antibody, in Combination With Gefitinib in Asian Patients With NSCLC. Issue 5 (18th January 2018) - Tan, Eng‐Huat; Lim, Wan‐Teck; Ahn, Myung‐Ju; Ng, Quan‐Sing; Ahn, Jin Seok; Shao‐Weng Tan, Daniel; Sun, Jong‐Mu; Han, May; Payumo, Francis C.; McKee, Krista; Yin, Wei; Credi, Marc; et al.
Abstract: Hepatocyte growth factor (HGF)/c‐Met pathway dysregulation is a mechanism for epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). Ficlatuzumab (AV‐299; SCH 900105), a humanized IgG1 κ HGF inhibitory monoclonal antibody, prevents HGF/c‐Met pathway ligand–mediated activation. This phase 1b study assessed the safety/tolerability, pharmacokinetics/pharmacodynamics, and antitumor activity of ficlatuzumab plus gefitinib in Asian patients with previously treated advanced non–small cell lung cancer (NSCLC). Patients received intravenous ficlatuzumab either 10 mg/kg (cohort 1; n = 3) or 20 mg/kg (cohort 2; n = 12) every 2 weeks plus oral gefitinib 250 mg daily. Patients tolerated the drug combination well. Four treatment‐related grade 3/4 adverse events were reported in 3 patients (cohort 2). Pharmacokinetic profiles for ficlatuzumab and gefitinib were consistent with prior single‐agent trials. Partial responses were achieved in 5 patients (4 confirmed), all in cohort 2; objective response rate (ORR) was 33% (duration, 1.9–6.4 months). Responding patients had no prior EGFR TKI treatment, 2 without an EGFR mutation. Four additional patients had disease stabilization (cohort 2; duration, 2.7–9.1 months; 42% ORR). The recommended phase 2 dose for ficlatuzumab plus gefitinib 250 mg/day was 20 mg/kg every 2 weeks. This drug combination has shown preliminary dose‐related antitumor activity in advanced NSCLC.